Predictive Performance of Artificial Neural Network and Multiple Linear Regression Models in Predicting Adhesive Bonding Strength of Wood - Bardak, S.; Tiryaki, S.; Bardak, T.; Aydin A. (Проблемы прочности, 2016)
The purpose of this study was to develop artificial neural network (ANN) and multiple linear regression (MLR) models that arecapable of predicting the bonding strength of wood base on moisture content, open assembly time and closed assembly time of the joints prior to pressing process. For this purpose, the experimental studies were conducted and the models basedon experimental results were set up. As a result of the experiments conducted, it was observed that bonding strength first increased and then decreased with increasing the wood moisture content and adhesive open assembly time. In addition, the increased closed assembly time caused a decrease in bonding strength of wood. The ANN results were compared with the results obtained from the MLR modelto evaluate the models’ predictive performance. It was found that the ANN model with the R² value of 97.7% and the mean absolute percentage error of 3.587% in test phase exhibits higher prediction accuracy than the MLR model. The comparison results confirm the feasibility of ANN model in terms of predictive performance. Consequently, it can be said that ANN is an effective tool in predicting wood bonding strength, and quite useful instead of costly and time-consuming experimental investigations. Разработаны нейронная сеть и множественные линейные регрессионные модели для оценки адгезионной прочности деревянных конструкций с учетом их влажности и времени полной сборки элементов конструкции до их прессования. Результаты проведенных экспериментальных исследований использовали в разработанных моделях. Показано, что при увеличении влажности и времени сборки адгезионная прочность вначале растет, а затем уменьшается. С повышением времени полной сборки адгезионная прочность снижается. Сравнение расчетных результатов, полученных с помощью искусственной нейронной сети и множественных линейных регрессионных моделей, свидетельствует о преимуществе первого подхода, согласно которому коэффициент корреляции R² = 97,7%, среднее отклонение составляет 3,587%. Установлено, что искусственная нейронная сеть является эффективной для прогнозирования адгезионной прочности деревянных конструкций, что позволяет сократить количество трудоемких и дорогостоящих экспериментальных исследований. Розроблено нейронні мережі і множинні лінійні регресійні моделі для оцінки адгезійної міцності дерев яних конструкцій з урахуванням їх вологості та часу повного складання елементів конструкції до їх пресування. Результати проведених експериментальних досліджень використовували в розроблених моделях. Показано, що зі збільшенням вологості і часу складання адгезійна міцність спочатку зростає, а потім знижується. Зі збільшенням часу повного складання адгезійна міцність знижується. Порівняння розрахункових результатів, отриманих за допомогою штучної нейронної мережі і множинних лінійних регресивних моделей, свідчить про переваги першого методу, згідно з яким коефіцієнт кореляції R² = 97,7%, середнє відхилення складає 3,587%. Установлено, що штучна нейронна мережа є ефективною для прогнозування адгезійної міцності дерев'яних конструкцій, що дозволяє скоротити кількість трудомістких і дорогих експериментальних досліджень.